Identification of root exudates from the Pb-accumulator Sedum alfredii under Pb stresses and assessment of their roles. Issue 1 (1st January 2017) - Luo, Qing; Wang, Shiyu; Sun, Li-na; Wang, Hui; Bao, Tong; Adeel, Muhammad
ABSTRACT: The Pb-accumulator Sedum alfredii is a good phytoremediation material, and widely used in the phytoremediation research of soils contaminated with Pb. The root exudates from it may be playing a significant role in the process of phytoremediation. In this study, the metabonomics method which based on gas chromatography–mass spectrometry (GC–MS) and pattern recognition analysis was used to identify the remarkable root exudates from S. alfredii under different Pb stresses, including exposure concentrations (0, 10, 50, 200 and 1000 µmol/L) and times (4 and 8 days). And batch extraction experiments were used to verify the roles of these remarkable root exudates. According to the results, 11 metabolites were considered as the remarkable metabolites. Oxalic acid, galactonic acid and glyceric acid can remove Pb in soil, and the removal effect was: oxalic acid > galactonic acid > glyceric acid. Xylose, glucose and maltose have no removal effect for Pb in soil.